Nanostructured self-cleaning lyocell fabrics with asymmetric wettability and moisture absorbency (part I) - Kwon, Seong-ok; Ko, Tae-Jun; Yu, Eusun; Kim, Jooyoun; Moon, Myoung-Woon; Park, Chung Hee (ROYAL SOC CHEMISTRY, 2014)
A single-faced superhydrophobic lyocell fabric maintaining its inherent high moisture absorbing bulk property was produced by oxygen plasma-based nanostructuring and a subsequent coating with a low-surface-energy material. After 5 minutes of oxygen plasma etching, followed by 30 seconds of a plasma polymerized hexamethyldisiloxane coating, the treated surface of lyocell turned into a superhydrophobic surface with a static contact angle greater than 160 degrees and a sliding angle less than 2 degrees; however, the backside was hydrophilic, untreated lyocell fabric. As a result of oxygen plasma etching, dual hierarchical roughness was formed on the lyocell fabric as nano scale pillars or hairs were added onto the lyocell fabric surface with micro scale roughness. Extremely opposite wetting behavior was observed, when a water droplet was deposited on the face and backside of the plasma-treated lyocell fabric. A water droplet was immediately absorbed and spread out on the untreated backside, while it rolled off the treated surface, demonstrating a bouncing effect.
Keywords: SURFACE; FIBERS; COATINGS